Biochemical Composition of Pumpkin Seeds and Seed By-Products - Nikolaos Polyzos; Ângela Fernandes; Ricardo C. Calhelha; Jovana Petrović; Marina Soković; Isabel C. F. R. Ferreira; Lillian Barros; Spyridon A. Petropoulos (Plants, 2024)
The goal of the current work was to assess the nutritional profile and phytochemical properties of cucurbit (Cucurbita maxima L.) seeds, seed oils and oil extraction by-products (e.g., seed-cakes). Our results suggest a high nutritional value for both cucurbit seeds and cucurbit cake, while γ-tocopherol was the richest compound, with traces of α, β and δ-tocopherol compounds also detected. Regarding the free sugars composition, there were recorded significant statistical differences between seeds and cucurbit seed-cake, although sucrose content was the highest for both matrices (1.97 and 2.9 g/100 g dw, respectively) followed by trehalose (0.26 and 0.25 g/100 g dw, respectively), fructose (0.20 and 0.34 g/100 g dw, respectively) and glucose (0.21 and 0.19 g/100 g dw, respectively). In terms of organic acids, oxalic was the only compound detected in seed cake (0.006 g/100 g dw), while in seeds only traces of oxalic and malic acid were detected. In relation to fatty acid composition, linolenic acid was the most abundant compound in both seeds and seed-cake (43.9% and 41.5%, respectively), while oleic acid (37.0% and 36.3%, respectively), palmitic acid (12.2% and 14.0%, respectively) and stearic acid (4.83% and 5.46%, respectively) were detected in lesser amounts. Moreover, polyunsaturated fatty acids (PUFA) were the major fatty acids class (44.5% and 42.3% in seeds and seed cake, respectively) compared to monounsaturated fatty acids (MUFA; 37.4% and 36.7% in seeds and seed cake, respectively) and saturated fatty acids (SFA; 18.1% and 21.0% in seeds and seed cake, respectively) which were detected in lower amounts. Furthermore, the tested extracts did not present any cytotoxic or hepatoxic activity at the maximum tested concentration (GI50 > 400 μg/mL), while seed oils presented satisfactory antimicrobial properties with inhibitory activity against the studied bacterial strains and fungi. Our findings provide valuable knowledge regarding the exploitation of pumpkin seeds and seed by-products as valuable natural sources of nutrients and phytochemicals in the food industry sector within the context of a circular economy.